The Socio-Economic Integration of Ethnic Minorities - Li, Yaojun (2017)
One of the most striking features of the contemporary world is the scale and complexity of international and internal migration and the rapidly increasing size of indigenous ethnic minorities in the national populations of many countries. International migration continues to be mainly from poor to rich nations but the more recent years have seen migration patterns becoming multidirectional, with migration flows moving between developed countries, amongst developing countries as well as from developing to developed countries. The scale of internal migration in some countries is dazzling. For instance, an estimated 260 million ‘peasant workers’ have moved to cities in China. The number of indigenous ethnic minorities in the country has also grown substantially, now reaching 106 million. These and other features of population change pose a serious challenge to policy-makers and the general population in many counties, in terms of making and implementing policies of social inclusion for migrant and indigenous ethnic minorities, ensuring equal access to educational and occupational opportunities, and taking measures to facilitate societal acceptance of the ethnic minority groups. With this in mind, we have, in this thematic issue, collected papers that address issues of ethnic integration in both developed and developing countries.